Glutamine deprivation alters the origin and function of cancer cell exosomes - Fan, Shih‐Jung; Kroeger, Benjamin; Marie, Pauline P; Bridges, Esther M; Mason, John D; McCormick, Kristie; Zois, Christos E; Sheldon, Helen; Khalid Alham, Nasullah; Johnson, Errin; Ellis, Matthew; Stefana, Maria Irina; et al. (The EMBO journal, 2020)
Exosomes are secreted extracellular vesicles carrying diverse molecular cargos, which can modulate recipient cell behaviour. They are thought to derive from intraluminal vesicles formed in late endosomal multivesicular bodies (MVBs). An alternate exosome formation mechanism, which is conserved from fly to human, is described here, with exosomes carrying unique cargos, including the GTPase Rab11, generated in Rab11‐positive recycling endosomal MVBs. Release of Rab11‐positive exosomes from cancer cells is increased relative to late endosomal exosomes by reducing growth regulatory Akt/mechanistic Target of Rapamycin Complex 1 (mTORC1) signalling or depleting the key metabolic substrate glutamine, which diverts membrane flux through recycling endosomes. Vesicles produced under these conditions promote tumour cell proliferation and turnover and modulate blood vessel networks in xenograft mouse models in vivo . Their growth‐promoting activity, which is also observed in vitro , is Rab11a‐dependent, involves ERK‐MAPK‐signalling and is inhibited by antibodies against amphiregulin, an EGFR ligand concentrated on these vesicles. Therefore, glutamine depletion or mTORC1 inhibition stimulates release from Rab11a compartments of exosomes with pro‐tumorigenic functions, which we propose promote stress‐induced tumour adaptation. Synopsis Heterogeneity of extracellular vesicles and their behaviour under metabolic stress conditions remain poorly understood. Here, reduction in glutamine levels or Akt/mTORC1 signalling are shown to induce cancer cell exosomes with altered cargos and increased pro‐tumorigenic functions, which are secreted from previously undescribed Rab11a‐dependent endosomes. Rab11a‐positive endosomal multivesicular bodies give rise to exosomes with distinct functions. Depletion of glutamine or Akt/mTORC1 induces Rab11a‐exosome release from cancer cells. Rab11a‐positive stress‐induced vesicles promote cancer cell and vessel growth in vitro and in vivo . An antibody against EGFR ligand, AREG, blocks Rab11a‐exosome‐induced tumour growth. Graphical Abstract Release of Rab11a‐positive exosomes with distinct cargos and increased pro‐tumorigenic functions is dependent on glutamine levels and Akt/mTORC1 signalling.